PENGARUH VARIASI PRODUK, KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA WEDDING ORGANIZER - titik efnita (Universitas Lancang Kuning, 2017)
Abstract: This research tries to know the product of great variation, qualitative service, price and location of CV.Modelman the research. The study consisted of four variables: product variation, service quality, price and location and one dependent customer satisfaction variable. The analytical method used. Method of data for this research using questionnaires distributed to respondents that consumer CV.Modelman as an object. Test results Reliability of SPSS 21 data processing obtained for each variable Kolmogorov-Smirnov> 0.06, ie 0.770 for product variation (X1), 0.741 for service quality (X2), 0.689 for price (X3). 0.719 for Locations (X4). 0.676 for consumer satisfaction (Y). From result of processing by using SPSS, regression model which can be analyzed as follows: Ŷ = 2,590 + 0,366 X1 + 0,164 X2 - 0,126 X3 + 0,877 X4. From the above equation obtained a constant price of 2,590, showing the product without. Product, service quality, price and location.Keywords: variation products , service quality , price, location